Faith no more? The divergence of political trust between urban and rural Europe. (August 2021) - Mitsch, Frieder; Lee, Neil; Ralph Morrow, Elizabeth
Abstract: Events such as Brexit and the Gilet Jaunes protests have highlighted the spatial nature of populism. In particular, there has been increasing political divergence between urban and rural areas, with rural areas apparently having lost faith in national governments. We investigate this divergence using data on over 125, 000 EU citizens from the European Social Survey from 2008 to 2018. We show that people in rural areas have lower political trust than urban or peri-urban residents, with this difference clear for six different forms of political institutions, including politicians, political parties, and national parliaments. There has been divergence of political trust between urban and rural Europe since 2008, although this is primarily driven by Southern Europe. While these results can partly be explained by demographic differences between cities and the countryside, divergent economic experiences, differences in values, and perceptions that public services are less effective outside of urban areas, there is a residual 'rural effect' beyond this. We argue that the polarisation of urban-rural political trust has important implications for the functioning of European democracies.